2014
DOI: 10.1371/journal.pone.0087150
|View full text |Cite
|
Sign up to set email alerts
|

Administration of a Probiotic Can Change Drug Pharmacokinetics: Effect of E. coli Nissle 1917 on Amidarone Absorption in Rats

Abstract: The growing interest in the composition and effects of microbiota raised the question how drug pharmacokinetics could be influenced by concomitant application of probiotics. The aim of this study was to find whether probiotic E. coli strain Nissle 1917 (EcN) influences the pharmacokinetics of concomitantly taken antiarrhythmic drug amiodarone (AMI). Live bacterial suspension of probiotic EcN (or non-probiotic E. coli strain ATCC 25922) was applied orally to male Wistar rats for seven days, while a control grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(46 citation statements)
references
References 26 publications
1
43
0
2
Order By: Relevance
“…Even so, it should be taken in account that results from animal experiments cannot be directly extrapolated to humans; however, bearing in mind the studies of Meng et al (55) and Shayeganpour et al (36), the rat appears to be an appropriate model for man in this case. Indeed, the mean peak plasma concentrations of amiodarone achieved in our work (Cmax 1.38 μg/mL and 0.95 μg/mL) are within the established drug therapeutic range (0.5-2 µg/mL) (36,37) and such concentrations were only slightly higher than the levels found in other studies performed in Wistar rats with same dosage (50 mg/kg) of amiodarone (Cmax 0.78 μg/mL and 0.84 μg/mL) (56).…”
Section: Discussionsupporting
confidence: 56%
“…Even so, it should be taken in account that results from animal experiments cannot be directly extrapolated to humans; however, bearing in mind the studies of Meng et al (55) and Shayeganpour et al (36), the rat appears to be an appropriate model for man in this case. Indeed, the mean peak plasma concentrations of amiodarone achieved in our work (Cmax 1.38 μg/mL and 0.95 μg/mL) are within the established drug therapeutic range (0.5-2 µg/mL) (36,37) and such concentrations were only slightly higher than the levels found in other studies performed in Wistar rats with same dosage (50 mg/kg) of amiodarone (Cmax 0.78 μg/mL and 0.84 μg/mL) (56).…”
Section: Discussionsupporting
confidence: 56%
“…The pharmacokinetics of an oral hypoglycaemic agent, gliclazide (administered as a single dose at 20 mg·kg −1 ), was significantly altered in diabetic rats pretreated with a cocktail of three probiotics ( Lactobacillus acidophilus , Lactobacillus rhamnosus and Bifidobacterium lactis ) for 3 days (Al‐Salami et al ., ). Similarly, probiotic treatment significantly altered the absorption of the anti‐arrhythmic agent amiodarone (Matuskova et al ., ). In this study, the probiotic E. coli strain Nissile (EcN) 1917 was administered to rats for 7 days, prior to a single p.o.…”
Section: Gut Microbiota–drug Interactionsmentioning
confidence: 97%
“…The E. coli strain Nissle 1917 increased amiodarone bioavailability in rats, while probiotic strains of L. casei slowed, although non-significantly, amiodarone absorption (Matuskova et al, 2014(Matuskova et al, , 2017. Kim et al showed that oral administration of L. reuteri K8 to mice reduced the area under the curve of acetaminophen compared with that of control mice (Kim et al, 2018).…”
Section: Probiotics and Pharmacologic Therapiesmentioning
confidence: 99%